Have British Jews fully assimilated in the UK Labour Market? - Nabil Khattab (RIMCIS, 2015)
This paper analyses the patterns of occupational attainment and earnings among the Jewish community in Britain using UK Labour Force Survey data (2002-2010). The findings suggest that although British-Jews cannot be distinguished from the majority main stream population of British-White in terms of their overall occupational attainment and earnings, it seems that they have managed to integrate through patterns of self-employment and concentration in the service sector economy, particularly in banking and financial services. It is argued that this self-employment profile is a Jewish strategy used to minimise dependency on majority group employers and by doing so to helping to escape any religious penalties.